Comics and enaction (Signifiances (Signifying), 2024)
This paper studies some of the possible relationships between comics and the linguistic theory of enaction. First, the relations between the discourse of the comic and the world will be discussed. I will show that they influence each other, although this influence in the comic may be controversial. Secondly, I will say a few words about embodiment in comics, focussing on the phenomena of planning and the semiotic resource of point of view. Finally, I will explain iconicity in the (verbal) language of comics, referring to onomatopoeia and lettering.